Radiation protection evaluation from radio diagnostic departments in Erbil hospitals - Younis, Saeed Nadhim; Ali, Runak Taher; Rashid, Sameeah Abdulrahman (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Radiation is used in some aspects of medicine, researches and in industries. These radiation applications are useful to society. However radiation can also have detrimental effects. It was important to establish rules and resolutions governing these uses to balance the positive against the negative effects. Dose limits have been established for groups who use radiation in their work as well as for population at large. The rules used in most countries have been worked out by the International Commission on Radiological Protection (ICRP). The aim of this study was to evaluate the radiation protective measures in different diagnostic radiological departments in Erbil hospitals. Methods: Data on the number of diagnostic procedures using x-ray examinations in five hospitals were collected. The palm RAD 907 Nuclear Radiation Meter and Contamination Monitor CoMo 170 were used to measure radiation leakage. Questionnaire was also used to elicit information from the most senior personnel of the hospital. Results: The finding showed that the facilities for safety were grossly inadequate and the dose rates of 16.4μSv/hr and 20μSv/hr were recorded at places for paramedics and technician room respectively. Dose rate in front of window of the monitor room was 113μSv/hr and in the reception was 20μSv/hr indicating higher health risk to the paramedic, visitors and personnel at the hospital. Conclusion: Radiation protection facilities in the radiological departments of Erbil hospitals are in general poor including both public & private sectors indicating high health risk to the paramedics, visitors and personnel at the hospitals